A rare thyroid disorder mimicking mitochondrial disease - Adrijan Sarajlija; Slađana Todorović; Biljana Alimpić; Maja Čehić (Биомедицинска истраживања, 2021)
Introduction: Patients affected with Allan-Herndon-Dudley syndrome (AHDS) have a deficiency of monocarboxylate transporter 8 (MCT8), a protein primarily responsible for the transport of triiodothyronine (T3) into the brain. This X-linked disorder affects almost exclusively males with clinical presentation encompassing developmental delay, axial hypotonia, dystonia, poor head control, quadriplegia and absence of speech. Case reports. Patient 1 is a male child referred to a hospital investigation at 11 months due to severe developmental delay and elevated blood ammonia level (163 mcmol/L). Hypotonia and dystonic movements were noted at admission, with facial dysmorphic features. Laboratory findings revealed increased blood lactate (17.2 mmol/L), alanine (533 mcmol/L) and ammonia (391 mcmol/L) concentrations. Serum creatine-kinase levels showed substantial increase over the course of hospitalization up to 6,855 IU/L. Clinical exome sequencing detected a novel hemizygous frameshift insertion c.1456insC in gene SLC16A2, predicted to cause loss of normal protein function either through protein truncation or nonsense-mediated mRNA decay. Segregation genetic testing of the family members revealed that mother, maternal uncle and maternal grandmother carry the same mutation in SLC16A2. The boy`s mother experienced learning difficulties through childhood while maternal uncle is severely affected by AHDS. Patient 2 is a boy referred to clinical geneticist due to severe psychomotor delay of unknown etiology. Moderate serum lactate elevation was the only laboratory abnormality during initial investigations. Diagnosis of AHDS was established by clinical exome sequencing, and subsequent hormonal evaluation revealed increased triiodothyronine (T3) level which corresponds well to genetic diagnosis. Conclusion: Presence of lactic acidosis and/or hyperammonemia in children with severe developmental delay is not specific for inborn disorders of energy production, such as mitochondrial disease. Clinicians should consider thyroid hormones profiling in cases of unexplained severe developmental delay in male children, especially if associated with axial hypotonia and dystonic movements.
Keywords: Allan-Herndon-Dudley syndrome; hyperammonemia; lactic acidosis